EVALUASI KINERJA KEUANGAN DAN KELEMBAGAAN KOPERASI SE-KOTA METRO - Juniansyah Juniansyah (Derivatif : Jurnal Manajemen, 2017)
In accordance with the cooperation that is cooperative economic activity is based on the cooperation of family. Hence the main objective of cooperatives is to improve prosperity of the members in particular and society in general. And for that in an effort to examine and evaluate performance of cooperatives in the process of reaching the goal is to there needs to be on the performance of the measurement of cooperative.The formulation of problems in this research is: 1) The how the performance of cooperatives in the city Metro based on KepMenKop and UKM No. 96 year of 2004? 2) the how the performance of cooperatives in the city Metro institutional based on analysis?, 3) the how the institutional design (coordination system) performance of cooperatives can be improved?.This study was conducted in the city metro, in this study the sample used as is 13 cooperatives in the city metro who has committed RAT accounting year 2014. Collection of samples non technique use probability sampling which is purposive the sampling method of. All kinds of analyses descriptive and analysis describes a summary of research data such as the mean, standard deviations, mode of etc. In this research will be conducted descriptive analysis with provide an illustration of data on the amount of data, minimum, maximum, and the average, then also all kinds of analyses the ratio based on KepMenKop and UKM No. 96 year of 2004.Of the analysis can be concluded that based on the ratio of the solvability of standards in general financial performance of cooperatives in the city metro is good, based on standards and the ratio of the solvability in general financial performance of cooperatives in the city metro also is good. Then based on analysis of the survey and interviews concluded of institution performance of cooperatives in the city metro is good.Keywords: Solvability, Rentability, Institution Performance.